Cultural Entertainment Consumption and Empathy Communication Mechanism - Zhang, Wenming (Frontiers in Psychology, 2022)
The economic and cultural effects of sports films have attracted close attention from the academia and the industry. Under the framework of community theory and empathy theory, this study applies network text analysis to expound the characteristics of interest-related community discourse practice in sports films, clarify the empathy mechanism performance of the interest-related community in sports films, and verify the general logic and mechanism characteristics through empirical exploration of the structural equation model. The research findings show that theme feature, brand building, technological innovation and spirit communication are the key factors that affect individual’s empathy for sports films, and they have a positive effect on affective empathy and cognitive empathy.